EFEKTIVITAS INFORMASI PERTANAHAN BERBASIS NOMOR OBYEK PAJAK (NOP) TERHADAP TRANSAKSI JUAL BELI TANAH DI KOTA SURAKARTA - SAMAD, AMRIANTO (Dinamika Hukum, 2018)
The background of the application of land information information based on Tax Object Number (NOP) to the land sale transaction in Surakarta City is obtaining an effective, efficient, and compatible Land Information System. The use of information technology for public services is a demand that must be provided by the government, including the Government of Surakarta. Information technology is a necessity of society because it not only helps communication and social interaction quickly, but also provides convenience in many ways.